Peran Pendidikan Bahasa Arab dalam Pengembangan Wisata Halal di Lombok - Nofi Fitria Indasari; Ali Fathurrahman (LP3M Sekolah Tinggi Agama Islam Nahdlatul Wathan SAMAWA SUMBAWA BESAR, 2022)
The Arabic learning and development of halal tourism in Lombok was developed because of the needs of the rapidly increasing national and global tourism market and as a tangible manifestation of the island's thousand mosques jargon. The seriousness of the NTB Regional Government in preparing halal tourism is evidenced through the ratification of the Regional Regulation of the Province of West Nusa Tenggara Number 2 of 2016 concerning Halal Tourism. This halal travel brand seems to be quite successful, because the statistics of tourist visits to Lombok show an increase. As an area that develops halal tourism, the NTB Regional Government must prioritize Arabic as a language of communication to provide maximum service to foreign tourists who are predominantly Muslim, and communicate in Arabic. This study aims to determine the Arabic language skills of guides on the island of Lombok. The research method used is qualitative with a field research model. The results showed that the ability of Arabic guides on Lombok Island is still very low, and this is due to the lack of training conducted by the NTB Regional Government as a form of support for the development of halal tourism. Therefore, the local government must collaborate with various Education that acclimates Arabic in its education process to improve Arabic language skills for guides, especially boarding schools in West Nusa Tenggara.